When too much adjustment is bad: A curvilinear relationship between expatriates' adjustment and social changes in HCNs - Sana Mumtaz; Sadia Nadeem (Cogent Business & Management, 2020)
The antecedents of expatriates' adjustment have received considerable attention in the international business research in the recent years. However, there has been a limited understanding regarding the outcomes of expatriates' adjustment on host country nationals (HCNs). Thus, examining the existing literature and analyzing it using social identity theory, we hypothesized an inverse curvilinear relationship between expatriates' interaction adjustment and development of trust, shared vision and intercultural communication in HCNs. We tested our hypotheses by conducting a multilevel regression analysis on dyadic data collected from Chinese expatriates and Pakistani HCNs. The findings confirm an inverse U-shape relationship between expatriates' interaction adjustment and trust, and between expatriates' interaction adjustment and intercultural communication. In contrast to the focus of existing literature on static changes, our findings highlight a dynamic nature of social change experiences by suggesting that too much adjustment of expatriates negatively impacts work relationships between expatriates and HCNs in the long-run. Based on the empirical findings, we offer insights to HR professionals and suggest managing expatriates' adjustment to an optimal level in a host unit where expatriates and HCNs can develop an adequate level of trust and intercultural communication with each other.
Keywords: 650; expatriates' adjustment; social identity theory; trust; shared vision; intercultural communication